2018
DOI: 10.1111/dme.13670
|View full text |Cite
|
Sign up to set email alerts
|

A retrospective observational study of people with Type 1 diabetes with self‐reported severe hypoglycaemia reveals high level of ambulance attendance but low levels of therapy change and specialist intervention

Abstract: We observed a high level of ambulance service intervention but surprisingly low levels of hypoglycaemia follow-up, therapy change and specialist intervention in people self-reporting severe hypoglycaemia. These results suggest there may be important gaps in care pathways for people with Type 1 diabetes self-reporting severe hypoglycaemia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 24 publications
1
6
0
Order By: Relevance
“…Despite development of effective hypoglycaemia pathways within emergency departments and ambulance services to primary, community and secondary care services for early review [2426], it has been reported that there are low levels of follow-up, therapy change and specialist input following an episode of hypoglycaemia [27]. This is in line with the clinical experience of the authors.…”
Section: Introductionsupporting
confidence: 69%
“…Despite development of effective hypoglycaemia pathways within emergency departments and ambulance services to primary, community and secondary care services for early review [2426], it has been reported that there are low levels of follow-up, therapy change and specialist input following an episode of hypoglycaemia [27]. This is in line with the clinical experience of the authors.…”
Section: Introductionsupporting
confidence: 69%
“…Even severe hypoglycaemia may not be captured in clinical notes or routine clinical review; episodes requiring Accident and Emergency department visits or hospitalization have been shown to go unreported to the direct care team in other real-world studies [15]. Even severe hypoglycaemia may not be captured in clinical notes or routine clinical review; episodes requiring Accident and Emergency department visits or hospitalization have been shown to go unreported to the direct care team in other real-world studies [15].…”
Section: Discussionmentioning
confidence: 99%
“…It is well known that hypoglycaemia is under-reported and poorly recorded. Even severe hypoglycaemia may not be captured in clinical notes or routine clinical review; episodes requiring Accident and Emergency department visits or hospitalization have been shown to go unreported to the direct care team in other real-world studies [15]. Data concerning hypoglycaemic events should be interpreted with caution in that 91% of participants prior to U300 initiation and 88% post-initiation of U300 had no documented mention of hypoglycaemia.…”
Section: Discussionmentioning
confidence: 99%
“…The study by Field et al [2] therefore makes worrying reading. The study by Field et al [2] therefore makes worrying reading.…”
mentioning
confidence: 98%
“…Given the clinical consequences of hypoglycaemia, one might have expected that efforts would be made to prevent further occurrences following an episode of severe hypoglycaemia. The study by Field et al [2] therefore makes worrying reading. They reported what happened after 140 episodes of severe hypoglycaemia in 85 people with Type 1 diabetes over a 2-year period.…”
mentioning
confidence: 98%